How Do Firms Form Their Expectations? New Survey Evidence - Coibion, Olivier; Gorodnichenko, Yuriy; Kumar, Saten (American Economic Review, 2018)
We survey New Zealand firms and document novel facts about their macroeconomic beliefs. There is widespread dispersion in beliefs about past and future macroeconomic conditions, especially inflation. This dispersion in beliefs is consistent with firms’ incentives to collect and process information. Using experimental methods, we find that firms update their beliefs in a Bayesian manner when presented with new information about the economy and that changes in their beliefs affect their decisions. Inflation is not generally perceived as being important to business decisions so firms devote few resources to collecting and processing information about inflation. (JEL D22, D83, D84, E31, E52)